SENSING THE PAST: AN EXPLORATION OF ART AND ARCHAEOLOGY - Poraj-Wilczynska, Elizabeth (Design/Arts/Culture, 2023)
This portfolio deals with the work I have been undertaking for the past 20 years. Investigating sense of place at Belas Knap Neolithic long barrow, Cotswolds, England. I have taken an holistic approach in the creation of art that aims to bridge the sensory experience of archaeology, memory and culture. Over the last twenty years I have been responding through my art to place and memory, mapping, interpreting and connecting to the seasonal changes at Belas Knap, a laterally chambered Neolithic long barrow located in the Cotswold Hills, Gloucestershire, South West England (NGR: SP0209 2554).